Cement hydration and durability of low sulfide tailings-based renders: A case study in Moroccan constructions. (15th May 2015) - Argane, R.; Benzaazoua, M.; Bouamrane, A.; Hakkou, R.
Highlights: Cement hydration and durability of low sulfide tailings-based renders were investigated. The use of low sulfide tailings as aggregates generates renders with higher porosity and lower portlandite content. The use of low sulfide tailings as aggregates lower resistance of renders to wetting/drying cycles. The use of low sulfide tailings as aggregates enhances resistance to sulfate attack. Incorporating tailings in renders successfully prevented the leaching of metals in conditions of acid rain. Abstract: Appropriate tailings management is one of the main requisites for sustainable development in the mining industry. This research study aims to assess the use of low sulfide or sulfide free tailings (LST) as aggregates for rendering mortars, focusing on their cement hydration and durability. An authentic case study in Moroccan constructions is additionally used to assess long term behavior of LST-based renders in actual field conditions. To address such needs, renders sampled from wall constructions and laboratory-made specimens were firstly characterized by means of thermo gravimetric analysis (TGA), X-ray diffraction analysis (XRD), scanning electron microscopy investigation (SEM) and mercury intrusion porosimetry (MIP). Renders were then exposed to standard detrimental agents (moisture, sulfate water and acid rain) to assess their long term behavior. Experimental results confirmed that LST-based renders seem to involve different cement hydration processes, which lead to larger pore size distribution and lower CSH and portlandite content. These observations significantly influence their susceptibility to cracking and sulfate attack resistance.